Boron removal from CEDI reject for water recycling - Kua, Han Wee (2016)
In the semiconductor industry, a large amount of water is used to rinse and clean and in wet processing, during which semiconductor devices are repeatedly dipped, immersed, or sprayed with solutions. Ultrapure water (UPW) is commonly used to minimize the risk of contamination, which is an essential requirement in the production of integrated circuits. Consequently, the production processes generate a huge volume of wastewater, which can be treated and reused. Continuous Electro Deionisation (CEDI) is usually applied after Reverse Osmosis (RO) to purify the RO product water to higher quality (Ultra) pure water. Usually the reject from CEDI could be recycled to be feed to the RO system. However, CEDI reject water contains significant amount of boron, which should be reduced before recycling as RO feed. While there are several technologies that can be used to separate boron, these methods are not efficient and cost-effective in the long term. As such, the method of using ion exchange resins has been proposed for boron removal. In this study, the efficiency of boron removal from aqueous solution was explored using boron selective resins DIAION CRB 03 and strong basic anion exchange resins DIAION SAT10L in a fixed bed column. The effect of two operating parameters, pH and space velocity (SV), on boron removal were evaluated to determine impact on the efficiency of boron removal by the resins. In addition, Yoon-Nelson and Thomas models were applied to predict the capacities and model parameters. The results showed that pH and SV have impact on the breakthrough and saturation times of the resins inside the column. Adsorption capacity increased with increasing pH and decreasing SV. Both DIAION CRB 03 and DIAION SAT10L at pH 10 and SV 15 achieved the highest adsorption capacity of 5.343 and 8.798 respectively. However, DIAION CRB 03 is more efficient and suitable to remove boron, as the resins would be replaced at lower frequencies. Also, the theoretical values obtained by Yoon-Nelson and Thomas models were accurate and consistent with the experiment results for both operation parameters and for both types of resins.